Are American homeowners locked into their houses? The impact of housing market conditions on state-to-state Migration - Alicia Sasser Modestino; Julia Dennett (Federal Reserve Bank of Boston, 2012)
U.S. policymakers are concerned that negative home equity arising from the severe housing market decline may be constraining geographic mobility and consequently serving as a factor in the nation's persistently high unemployment rate. Indeed, the widespread drop in house prices since 2007 has increased the share of homeowners who are underwater on their mortgages. At the same time, migration across states and among homeowners has fallen sharply. Using a logistic regression framework to analyze data from the Internal Revenue Service on state-to-state migration between 2006 and 2009, the authors discover evidence that house lock decreases mobility but find it has a negligible impact on the national unemployment rate. A one-standard deviation increase in the share of underwater nonprime households in the origin state reduces the outflow of migrants from the origin to the destination state by 2.9 percent. When aggregated across the United States, this decrease in mobility reduces the national state-to-state migration rate by 0.05 percentage points, resulting in roughly 110,000 to 150,000 fewer individuals migrating across state lines in any given year. Assuming that all of these discouraged migrants were job-seekers who were previously unemployed before relocating and then found a job in their new state would reduce the nation's unemployment rate by at most one-tenth of a percentage point in a given year. The cumulative effect over this period would yield an unemployment rate of 9.0 percent versus 9.3 percent in 2009. Recognizing that not all state-to-state migrants are job-seekers, not all job-seekers were previously unemployed, and not all previously unemployed job-seekers will successfully find work in their new location yields an unemployment rate that is virtually unchanged from the actual one that prevailed from 2006 to 2009.
Keywords: J61; R23; 330; negative equity; geographic labor mobility